1998
DOI: 10.1016/s0002-9440(10)65643-x
|View full text |Cite
|
Sign up to set email alerts
|

Brain Trauma Induces Massive Hippocampal Neuron Death Linked to a Surge in β-Amyloid Levels in Mice Overexpressing Mutant Amyloid Precursor Protein

Abstract: Although brain trauma is a risk factor for Alzheimer's disease, no experimental model has been generated to explore this relationship. We developed a model of brain trauma in transgenic mice that overexpress mutant human amyloid precursor protein (PDAPP) leading to the appearance of Alzheimer's disease-like beta-amyloid (Abeta) plaques beginning at 6 months of age. We induced cortical impact brain injury in the PDAPP animals and their wild-type littermates at 4 months of age, ie, before Abeta plaque formation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 134 publications
(96 citation statements)
references
References 27 publications
5
90
1
Order By: Relevance
“…In addition to human studies, the effects of TBI on A␤ and AD pathology have also been studied using TG mouse models of AD. Smith et al (1998) reported that TBI in PDAPP mice resulted in an 84% loss of CA3 neurons compared with only a 36% loss in non-TG mice. Nakagawa et al (1999Nakagawa et al ( , 2000 have reported that TBI in both young and old PDAPP mice induces atrophy and reduces A␤ deposition in the ipsilateral versus contralateral hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to human studies, the effects of TBI on A␤ and AD pathology have also been studied using TG mouse models of AD. Smith et al (1998) reported that TBI in PDAPP mice resulted in an 84% loss of CA3 neurons compared with only a 36% loss in non-TG mice. Nakagawa et al (1999Nakagawa et al ( , 2000 have reported that TBI in both young and old PDAPP mice induces atrophy and reduces A␤ deposition in the ipsilateral versus contralateral hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Knockout APOE mice subjected to weight-drop brain injury were found to have exacerbated memory impairment and motor deficits, when compared to wild-type controls. In mouse studies, 10-fold over-expression of mutant APP leads to the development of plaques at 6 months of age, with TBI exacerbating cognitive impairments and hippocampal CA3 pathology compared with littermates (Smith et al, 1998). In addition to Alzheimer's disease, TBI may also be a risk factor for other neurodegenerative diseases, including Parkinson's disease, characterized by intracellular filament occlusions in neurons (Hubble et al, 1993).…”
Section: Genetic Aspects Of Stroke and Head Traumamentioning
confidence: 99%
“…66,85,87,88 Briefly, the MWM is a circular pool 1 m in diameter that is painted white inside. 65 The water (16-18˚C) filling the pool is made opaque by adding nontoxic, watersoluble white paint.…”
Section: Assessment Of Cognitive Functionmentioning
confidence: 99%
“…Scores were assigned according to time spent in various zones of the MWM, and a memory score was calculated weighting the time spent in each zone according to the proximity to the previous platform site. 66,85,87,88 To test for impairment of learning ability, a separate group of mice (15 sham-injured animals, 16 animals subjected to a single TBI, and 16 animals subjected to an RHI) received no training in the MWM prior to injury. At 56 days postinjury, these animals were tested for their ability to learn the visuospatial task in the MWM over a 2-day period, following the identical protocol described earlier, and were tested the following day (Day 58) for retention of the learned task (probe trial), details of which were originally described in the rat.…”
Section: Assessment Of Cognitive Functionmentioning
confidence: 99%
See 1 more Smart Citation